The Higgs boson decay h → bs in the U(1) X SSM - Song Gao; Shu-Min Zhao; Ming-Yue Liu; Xing-Yu Han; Xi Wang; Tai-Fu Feng (Journal of High Energy Physics, 2024)
Abstract In the U(1) X SSM, we delve into the quark flavor violation of h → bs, where h is identified as the SM-like Higgs boson discovered at the LHC. As the U(1) extension of the minimal supersymmetric standard model (MSSM), the U(1) X SSM has new super fields such as right-handed neutrinos and three Higgs singlets. We conduct a thorough analysis of the underlying mechanisms and parameter dependencies of h → bs in the U(1) X SSM. In the U(1) X SSM, we discover that the Br(h → bs) for the Higgs decay to bs could significantly differ from the expectation in the standard model (SM), depending on the values of the new parameters introduced in the model. Our research not only contributes to a deeper understanding of Higgs physics within the U(1) X SSM, but also provides valuable guidance for new physics (NP).